Use of the Satinsky clamp for hilar clamping during robotic partial nephrectomy: indications, technique, and multi-center outcomes. Issue 1 (March 2017) - Abdullah, Newaj; Rahbar, Haider; Barod, Ravi; Dalela, Deepansh; Larson, Jeff; Johnson, Michael; Mass, Alon; Zargar, Homayoun; Kaouk, Jihad; Allaf, Mohamad; Bhayani, Sam; Stifelman, Michael; et al.
Abstract A Satinsky clamp may be a backup option for hilar clamping during robotic partial nephrectomy (RPN) if there are challenges with application of bulldog clamps, but there are potential safety concerns. We evaluate outcomes of RPN using Satinsky vs. bulldog clamps, and provide tips for safe use of the Satinsky as a backup option. Using a multi-center database, we identified 1073 patients who underwent RPN between 2006 and 2013, and had information available about method of hilar clamping (bulldog clamp vs. Satinsky clamp). Patient baseline characteristics, tumor features, and perioperative outcomes were compared between the Satinsky and bulldog clamp groups. A Satinsky clamp was used for hilar clamping in 94 (8.8 %) RPN cases, and bulldog clamps were used in 979 (91.2 %) cases. The use of a Satinsky clamp was associated with greater operative time (198 vs. 175 min, p  < 0.001), estimated blood loss (EBL, 200 vs. 100 ml, p  < 0.001), warm ischemia time (WIT, 20 vs. 19 min, p  = 0.036), transfusion rate (12.8 vs. 4.8 %, p  = 0.001), and hospital stay (3 vs. 2 days, p  < 0.001). Tumor characteristics and number of renal vessels were similar between groups. There were six intraoperative complications in the Satinsky clamp group, but none were directly related to the Satinsky clamp. On multivariable analysis, the use of the Satinsky clamp was not associated with increase in intraoperative or Clavien ≥3 postoperative complications, positive surgical margin rate or percentage change in estimated glomerular filtration rate. A Satinsky clamp can be a backup option for hilar clamping during challenging RPN cases, but requires careful technique, and was rarely necessary.